2007
DOI: 10.2478/s11687-007-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of praziquantel baiting on intestinal helminths of foxes in southwestern Germany

Abstract: SummaryFox baits containing 50 mg praziquantel were distributed by aircraft in a 3000 km 2 area of southwestern Germany from 1995 to 1999. 20 baits / km 2 were initially distributed at intervals of six to twelve weeks. Starting from a prebaiting prevalence of 64 % (95 % C.I. 59 -69), a level of 15 % (C.I. 10 -21) was reached after 18 months. Further decreasing the frequency and discontinuing the bait distribution caused a surge to 55 % (C.I. 49 -61) within 36 months. Other cestode species (Taenia spp., Mesoces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…There are many probable reasons for fluctuations in the hare population in Europe; however, deterioration of animal health strongly influenced by anthropization of landscape seems to be the key factor. Hares suffer considerably from predation, particularly by foxes (Newey et al, 2007;Romig et al, 2007;Di Cerbo et al, 2008;Miterpáková et al, 2009), and the decline was accompanied by a growth in predators in recent years. The population density may also be influenced by different diseases, some of them occurring only locally.…”
Section: Introductionmentioning
confidence: 99%
“…There are many probable reasons for fluctuations in the hare population in Europe; however, deterioration of animal health strongly influenced by anthropization of landscape seems to be the key factor. Hares suffer considerably from predation, particularly by foxes (Newey et al, 2007;Romig et al, 2007;Di Cerbo et al, 2008;Miterpáková et al, 2009), and the decline was accompanied by a growth in predators in recent years. The population density may also be influenced by different diseases, some of them occurring only locally.…”
Section: Introductionmentioning
confidence: 99%
“…Our results confi rm the high potential of E. multilocularis to recover to a precontrol level within a short period if the parasite was not completely removed, as has been predicted by modeling studies (14,15) and shown in a single, but large, baiting area in Germany (6). On the basis of a spatially explicit model, Hansen et al recommend continued bait delivery with intervals from 4 to 6 weeks (15).…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, small baiting areas are more affected by border effects. Further decreasing the baiting frequency to 6-month intervals and discontinuing bait distribution caused a surge of E. multilocularis prevalence in foxes to the precontrol level within 36 months (6).…”
Section: Discussionmentioning
confidence: 99%
“…Rodents can transmit infectious agent also to domestic carnivores, facilitating transmission of the disease to man (Hildebrand et al, 2009). Therefore, preventive measures, for example anthelmintic bait distribution that decreases E. multilocularis prevalence in definitive hosts (Antolová et al, 2006;Romig et al, 2007), should be applied to reduce infection pressure on men in hyperendemic areas.…”
Section: Discussionmentioning
confidence: 99%